The Phenomenology of Parkinson's Disease - Hess, Christopher W.; Hallett, Mark (Seminars in Neurology, 2017)
The motor symptoms of Parkinson's disease are not limited to the cardinal symptoms of bradykinesia, rigidity, and resting tremor, but also include a variety of interrelated motor phenomena such as deficits in spatiotemporal planning and movement sequencing, scaling and timing of movements, and intermuscular coordination that can be clinically observed. Although many of these phenomena overlap, a review of the full breadth of the motor phenomenon can aid in the diagnosis and monitoring of disease progression.
Keywords: Parkinson's disease; phenomenology; symptoms; signs